Simulacra and Hyperreality: Fashion Influencer Instagram @farhanabodi - Rasdica Denara Hernowo Puteri (Universitas Islam Darul Ulum Lamongan, 2023)
This paper aims to understand simulacra, hyperreality and symbolic diffusion of social media content presented by fashion influencers on the Instagram fashion influencer @farhanabodi account through case studies of social media content. Social media influencers are ideal role models for consumer society in the digital era. Manufacturers manipulate the utility of a product by creating advertisements or campaigns that use social media influencers to display images related to the product. Jean Baudrillard, French philosopher and postmodern cultural theorist, reads social phenomena under the influence of a new era of digital products, which he calls consumer society. Based on Baudrillard's thoughts on media and technology criticism and human behavior, there are two problems in studying fashion influencer social media content, namely first, what is the form of simulacrum, hyperreality in fashion influencer content and second, what effect does it have on followers' consumption behavior? This study leads to an investigation that the social media content of fashion influencers varies from the form of a simulacrum mechanism to the emergence of